Valuing Marine Reserves: A case study from two locations in central New Zealand. (June 2022) - Rojas-Nazar, Ursula A.; Gardner, Jonathan P.A.; Rouchon, Agnes; Cullen, Ross
Abstract: Marine protected areas such as full no-take marine reserves (MRs) supply numerous ecosystem goods and services, and also deliver conservation and biodiversity benefits, but there are few studies reporting how much the general public values MRs and what factors influence their Willingness to Pay (WTP) for MR management and protection. This study uses Contingent Valuation Method to estimate the WTP of nearby residents for management of two New Zealand MRs (Taputeranga and Kapiti). A total of 360 questionaries were completed (TMR = 262 and KMR = 98). Respondents were asked if they would contribute an annual levy to fund MR management. The annual median WTP values per household were NZ 22.50 (TMR) and NZ 16.88 (KMR). This analysis showed that respondent with children (TMR) or belonging to a group (KMR) are more willing to contribute to the levy. Age is an explanatory variable for WTP amount at both MRs. Respondents ranked seven options for how funds provided via the annual levy should be used; At both MRs more surveillance to reduce fishing at MRs boundaries, and clearing the beach of litter, were ranked highest. This article provides clear evidence that respondent households attach significant value to MRs located on the coast of their city. Findings of this research may be used by the New Zealand Department of Conservation to help prioritise its spending for the maintenance of existing MRs. Highlights: Marine Protected Areas, including Marine Reserves (MRs), are underfunded globally and in New Zealand. Use and non-use values of MRs are unknown in New Zealand. Contingent Valuation was used to estimate indirect use and non-use values of MRs. Social factors were identified that influence willingness to contribute to MR management. Recommendations can be made based on willingness to contribute to help prioritise MR funding and policies.